2019
DOI: 10.3390/vaccines7030102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Vesicles in Viral Infection and Transmission

Abstract: Extracellular vesicles (EVs) have been found to be released by any type of cell and can be retrieved in every circulating body fluid, namely blood (plasma, serum), saliva, milk, and urine. EVs were initially considered a cellular garbage disposal tool, but later it became evident that they are involved in intercellular signaling. There is evidence that viruses can use EV endocytic routes to enter uninfected cells and hijack the EV secretory pathway to exit infected cells, thus illustrating that EVs and viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
170
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 135 publications
1
170
0
Order By: Relevance
“…Similar findings were reported for poliovirus [115] and zikavirus [116]. Moreover, it has been widely reported that enveloped viruses hijack the endosomal-lysosomal pathway for biogenesis and infection [117]. As a matter of fact, EVs and viruses share common features in their size, biogenesis and uptake and, when released by infected cells, EVs have been demonstrated to contain viral components, such as proteins and genetic material [118].…”
Section: Non Degradative Function Of Autophagy: Secretory Autophagysupporting
confidence: 79%
See 1 more Smart Citation
“…Similar findings were reported for poliovirus [115] and zikavirus [116]. Moreover, it has been widely reported that enveloped viruses hijack the endosomal-lysosomal pathway for biogenesis and infection [117]. As a matter of fact, EVs and viruses share common features in their size, biogenesis and uptake and, when released by infected cells, EVs have been demonstrated to contain viral components, such as proteins and genetic material [118].…”
Section: Non Degradative Function Of Autophagy: Secretory Autophagysupporting
confidence: 79%
“…The elevated α-synuclein exocytosis promoted α-synuclein deposition and cell death in neighboring neurons [127]. This finding provides a potential link between autophagic dysfunction and the progressive spread of the pathology [117]. In the case of Alzheimer's disease (AD), very early evidence for the role of MVBs in βAPP metabolism was provided by the study by Vingtdeux et al, which showed that βAPP and its catabolic derivatives are secreted in exosomes [62].…”
Section: Non Degradative Function Of Autophagy: Secretory Autophagymentioning
confidence: 99%
“…The composition of each kind of EV derives from the cell and purpose of the vesicle realized to the media. As such, these vesicles became an important marker for diseases, including cancer, infectious diseases, renal diseases, and diabetes [16][17][18][19][20]. In order to achieve this, EVs must be characterized and analyze their confidence to be candidates for those used by humans.…”
Section: Study Of Evsmentioning
confidence: 99%
“…They are considered as both inter and intra-cellular messengers, able to modify their cargo according to the condition or stimulus affecting the parent cells [31,32], which upon internalization by recipient cells, can modulate the pathophysiological state in those cells [33,34]. EVs play an important role in HIV pathogenesis -either in improving or deteriorating the existing condition; however, the exact role of EVs in HIV pathogenesis is poorly understood [35,36]. Currently, only a handful of studies have investigated the role of EVs in smoking-mediated toxicity in the setting of HIV [37][38][39].…”
Section: Introductionmentioning
confidence: 99%